Effects of plasma surface treatment on the bond strength of zirconia with an adhesive resin luting agent - Miura, Shoko; Fujisawa, Masanori; Vallittu, Pekka; Lassila, Lippo (Japanese Society for Dental Materials and Devices, 2025)
The purpose of this study was to evaluate the effect of the atmospheric pressure plasma treatment as a surface treatment method on the contact angle and shear bond strength (SBS) of zirconia ceramics and the failure mode between the self-adhesive resin luting agent and zirconia. The zirconia specimens were divided into eight groups based on the surface treatment method: alumina blasting, air plasma, argon plasma (AP), Katana cleaner, ozonated water, ozonated water+AP, Katana cleaner+AP, and tap water+AP. The contact angles, SBS, and fracture modes were tested. AP treatment significantly reduced the contact angle (p<0.0001). The combination of AP and other cleaning methods showed a higher bond strength and more mixed fractures. Our findings indicate that using atmospheric pressure plasma with argon gas, combined with other cleaning methods, results in a stronger bond than when using alumina blasting alone.